2023
DOI: 10.1007/s00167-023-07581-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ankle and hip joints following medial opening‐wedge high tibial osteotomy affect knee joint line obliquity

Sang‐Gyun Kim,
June‐Bum Jun,
Il Wook Bae
et al.

Abstract: Purpose This study aimed to measure the change in knee joint line obliquity (KJLO) and the changes in radiologic parameters of the ankle and hip joints after medial opening-wedge high tibial osteotomy (MOWHTO), and to evaluate the correlation and causal relationship between these parameters. Methods This study evaluated 109 patients who underwent MOWHTO between April 2015 and December 2021. Radiologic parameters, including KJLO, medial proximal tibial angle (MPTA), ankle joint line obliquity (AJLO), and hip ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…A brace test for instance may help to identify these patients [24]. Another point to note is the ankle joint alignment which is reported, following MOWH-TO, to improve from preoperative valgus malalignment to postoperative neutral [15] Additionally, a recent study reported that MOWHTO increases knee joint line obliquity and results in hip adduction and ankle valgisation [16]. Furthermore, the postoperative ankle joint alignment angle was reported to significantly contribute to increased knee joint line obliquity following MOWHTO, hence should be accounted for in the preoperative planning [33].…”
Section: Discussionmentioning
confidence: 99%
“…A brace test for instance may help to identify these patients [24]. Another point to note is the ankle joint alignment which is reported, following MOWH-TO, to improve from preoperative valgus malalignment to postoperative neutral [15] Additionally, a recent study reported that MOWHTO increases knee joint line obliquity and results in hip adduction and ankle valgisation [16]. Furthermore, the postoperative ankle joint alignment angle was reported to significantly contribute to increased knee joint line obliquity following MOWHTO, hence should be accounted for in the preoperative planning [33].…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly due to a compensatory effect provided by the change in orientation in the ankle joint relative to the ground, facilitated by subtalar joint mobility (60,61). Following the valgus osteotomy of the proximal tibia, the ankle JLO also transitions from varus to a neutral alignment (62).…”
Section: Factors Associated With Postoperative Jlo In Medial Open Wed...mentioning
confidence: 99%
“…However, it has a less strong effect compared to changes in ankle loading. This is likely due to the distance from the knee and the correction of JLCA, which mitigates femoral adduction (62).…”
Section: Factors Associated With Postoperative Jlo In Medial Open Wed...mentioning
confidence: 99%